Propuesta de un sistema de información para apoyar la operación de modelos de educación en situación de emergencia: caso círculos de aprendizaje (2014)
This article presents the results of an investigation that was to support, with information systems - SI, the operation of the Learning Circles educational model by the University of Magdalena, in the framework of the Learning Circles Project - PCA. Development Information Systems from Soft Systems Thinking - DSI was selected as research methodology, also, the Human Activity Systems - HAS of Soft Systems Methodology - MSB were used to model the system proposed. The main results were: to defne the main system for PCA and the subsystems for educational, psychological and management components. Likewise, the conceptualization of information technology tools - IT that supports the execution of the activities of these components. Finally, this research shows how the SI and IT can support areas such important as education in emergency conditions, especially extreme poverty and displacement, and applied research to the problems of context.